Usability, environmental impacts and costs of internal combustion vehicles and electric vehicles (TRIM. Tordesillas, revista de investigación multidisciplinar, 2020)
A review of the usability, environmental impacts and costs that have been reported in previous research on the use of vehicles of the internal combustion engine, electric batteries and hybrids is carried out. Initially, its development and evaluations made by different groups of researchers are reviewed. It can be seen how over time advantages are added to the use of electric vehicles over internal combustion. As regards internal combustion vehicles, advantages are observed in the use of diesel with respect to gasoline.
Keywords: climate change; environmental impacts; usability; internal combustion vehicle; battery electric vehicle; hybrid vehicle